The Pemeringkatan Penanganan Covid-19 di Kawasan Asia Menggunakan AHP-COPRAS - Taufan Cahya Laksana; Setyawan Wibisono (STEKOM PRESS, 2022)
In this study, a ranking of the handling of Covid-19 in Asian countries was carried out using the AHP-COPRAS hybrid method. The ranking process uses the COPRAS (Complex Proportional Assessment) method, while the determination of the weight value uses subjective weighting but the criteria weights through a validation process using pairwise comparison which is part of the AHP (Analytical Hierarchy Process) method. The ranking process uses six assessment criteria: test per population, to positive per test, positive per population, healed per positive, died per positive, active per positive. The final result of the ranking shows that countries with high death cases and low cure cases will make the country's ranking fall, because cases of death and healing cases have the highest weight in their role in forming utility values.